Investigation of Noise Induced Hearing Loss at Shipyard Company, Surabaya - Yudhiakuari Sincihu; Steven Steven; Mulya Dinata; Melani Taurusia (Universitas Airlangga, 2019)
Introduction: Noise is a health risk that cannot be avoided in production process. Noise has the potential to cause hearing loss for workers. The bad news, noise damage due to noise is permanent. Audiometric screening at shipyard company employees found 81.2% experienced Sensory-Neural Hearing Loss. 61.5% of employees experience deafness in both ears. The research objective was to find the cause of deafness at shipyard company. Methods: A Quantitative research with cross sectional approach in 64 subjects who worked in the ship repair production unit. The sample is chosen with a simple random technique according to inclusion and exclusion criteria. Assessment was carried out using questionnaires, measurement, and direct observations. Result: The bad habit of wearing ear protectors on employees as a cause of deafness (p<.001, Coef .517**). Sound level measurement shows the activity of chipping, welding, cutting and outfitting with noise intensity more than the recommended threshold (85 dBA for 8 hour per day). Noisy sources were found such as blowers, compressors, grinders, cutting mach ines, ringlet machines, hammer blows on plates and generators. Conclusion: Hearing loss in shipyard company employees is a work-related disease caused by the poor culture of wearing ear protectors. The habits does not wear earplug/earmuff tools because its not comfortable in the ear when the appliance is used, the tools too small so its easily lost, forgetten to carry, and tool are not available.